COMPARATIVE STUDIES ON RESPIRATION : I. INTRODUCTION. - Osterhout, W. J. V. (The Rockefeller University Press, 1918)
A series of investigations on respiration with improved quantitative methods has been commenced. The first of these are here described. They show that when anesthetics are employed in sufficient concentration to produce any result, plants show a rise in the rate of respiration which is followed by a fall. In the animals studied, the rise (found in higher concentrations only) was preceded by a temporary fall which is not entirely due to lowering of muscular activity or tonus. In lower concentrations the effect on animals was merely a decrease of respiration. The results of all the investigations are opposed to the theory of Verworn.